Penerapan Media Pembelajaran untuk Meningkatkan Kemampuan Kognitif Anak Usia Dini - Salsabila Hasan; Oktavia Nusi; Susana Daito; Pupung Puspa Ardini; Gustin Lihawa; Astria Maili; Amelia Kadir (Jurnal Pendidikan Bahasa dan Anak Usia Dini, 2026)
The ability to recognize colors is one of the cognitive development aspects that should be stimulated from an early age. Color recognition helps children develop the ability to classify objects, think logically, improve memory, and better understand their surrounding environment. One strategy that can be used to stimulate this ability is through educational games that are engaging and appropriate for children's developmental characteristics. The "Fruit & Color Matching Adventure" game is an educational learning medium designed to help children recognize colors by matching pictures of fruits with their corresponding colors. This study aims to analyze the effectiveness of this educational game as a learning medium in supporting the cognitive development of early childhood. The method employed is a literature review, which analyzes various previous studies related to color recognition, interactive learning media, and early childhood cognitive development. The findings indicate that color-matching games can improve children's classification skills, visual discrimination, attention, concentration, and logical thinking abilities. Learning media that utilize concrete images, such as fruits, also help children understand color concepts more meaningfully. Therefore, the "Fruit & Color Matching Adventure" game has the potential to serve as an effective learning medium for enhancing the cognitive development of early childhood.